SETTING PARAMETER PROSES PEMASANGAN LID CUP AIR MINUM DALAM KEMASAN (AMDK) DENGAN METODE TAGUCHI - Agus Setiawan; Enty Nur Hayati; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2012)
Quality standards is one of the production costs, so if quality standards are properly executed will be able to reduce production costs. As was the case on the production floor CV Olympic Makmur Jaya as a producer of bottled drinking water (bottled water), which is in the process of production is still experiencing a lot of defects. bottled water products are often experienced is the kind of drinking water production defects cup 240 ml, so that the formulation of the research problem is how to set parameters lid machine mounting cup 240 ml drinking water that can improve the quality of the production process. The method used to solve this problem is the Taguchi experimental design. Taguchi experimental design is used to get the combination level parameter settings factors cup lid machine mounting that the installation process can improve the quality of drinking water 240 ml cup lid. The use of the Taguchi method is also based on minimizing the cost and duration of the experiment. From the data processing and analysis were done then it can be concluded that some combination of parameter settings factors proposed level of experimental results is heather temperature factor with levels 180° C (A1) , the level of aluminum mat thickness 2.5 cm (B1), and engine speed with 84 levels cup per minute (C2). Setting parameters of this proposal can reduce the function of a loss of 52.16% for each of the boxes of bottled drinking water products 240 ml cup. Kata kunci : Kualitas, Metode Taguchi, Cacat produksi